Aqua(iminodiacetato-κ3O,N,O′)(1,10-phenanthroline-κ2N,N′)cobalt(II) monohydrate - Hwa Loong Ng (Acta Crystallographica Section E, 2009)
The iminodiacetate dianion in the title compound, [Co(C4H5NO4)(C12H8N2)(H2O)]·H2O, chelates to the cobalt(II) atom, its N and two O atoms occupying the fac sites of the distorted octahedron around the metal atom. The metal atom is also chelated by the N-heterocycle. The dianion, and coordinated and uncoordinated water molecules interact through hydrogen bonds, generating a layer motif. The crystal studied was a racemic twin with a 0.62 (2):0.38 (2) domain ratio.